THE ROLE OF IL1Β CANDIDATE GENE POLYMORPHISMS IN THE OCCURRENCE OF MYOCARDIAL INFARCTION AND MULTIVESSEL DISEASE IN PATIENTS WITH CORONARY ARTERY DISEASE - O. L. Barbarash; J. V. Bairakova; A. V. Ponasenko; M. V. Khutornaya; A. A. Kuzmina; Y. V. Kazachek; L. S. Barbarash (Атеросклероз, 2016)
Objective: To evaluate the contribution of IL1β gene polymorphisms rs1143634 and rs16944 in the development of myocardial infarction (MI) and multivessel coronary artery disease in patients with CAD. Material and Methods: 303 patients with stable coronary artery disease were included in the study. Serum IL1β levels were measured with commercial kits (Bender MedSystems, Austria). TaqMan genotyping assays were performed in 96-well plate. Results: Women, who were homozygous carriers of the IL-1β rs1143634 G major allele, had a 4-fold decreased risk of developing multivessel coronary artery disease (p = 0.046) as well as a 2-fold decreased risk of myocardial infarction (p = 0.0198). The variable site of the IL1β rs1143634 was significantly (p = 0.0025) associated with a reduced risk of MI according to the dominant inheritance pattern (OR = 0.48, 95% CI = 0.29- 0.77), and rs16944 - with a five-fold increased risk (p = 0.0022) according to the co-dominant model (OR = 5.12, 95% CI = 1.82-14.42). The risk of myocardial infarction in men, who were homozygous carriers of the IL1β rs16944 T minor allele, was six times higher than that in women (p = 0.0093). The AC haplotype (rs1143634- rs16944) was associated with a 2-fold reduced risk of myocardial infarction and PICS (OR = 0.49, 95% CI = 0.29-0.81, p <0.0059), with the most pronounced effects in the age of 65 years (p = 0.0031). However, the GT haplotype rs1143634-rs16944 in younger patients (<65 years) was associated with the development of myocardial infarction (p = 0.0074). Conclusion: Genetic markers should be taken into consideration as an independent predictors of myocardial infarction and multivessel coronary artery disease.